Moving from Vulnerability to Resilience: A Climate Change Adaptation Plan for the Taunton River Watershed. - Plocinski, Loni. (2017)
Abstract: Ecosystems generate a variety of goods and services, collectively called ecosystem services, that sustain and fulfill human life. Climate change will affect the quality, abundance, distribution, productivity and value of ecosystem services throughout the Taunton River Watershed. This plan focuses on a subset of the watershed's ecosystem services and examines each through the lens of climate and non-climate stressors, vulnerabilities and equity and environmental justice issues. Economic data, where readily available, are also presented in order to contextualize the value of the selected ecosystem services and the impact, in terms of financial gains and losses, of healthy and impaired ecosystems in the watershed. Adaptation recommendations are included in order to increase the resilience of the river, and the physical resources that are connected to it, in light of the changing social, physical and environmental conditions in the watershed.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Scott Horsley.; Keyword: Climate change.